Islamic Religious Moderation of Non-Religion Major Students in Higher Education: A Quantitative Study - Mudra, Heri; Lia Angela (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Islamic religious moderation is mainly concerned with engaging those with or without ample comprehension to practice tolerable attitudes throughout academic life. This current study aimed to explore non-religion major students’ perceptions towards Islamic religious moderation practices in higher education atmospheres. A number of 157 students were involved to complete Religious Moderation Questionnaire as the main study instrument. The results showed that the students were mostly engaged in activities that support religious moderation thoughts. Although such moderation was not fulfilled, the students were able to cope with Islamic activities in university. They had various attitudes in perceiving religious moderation in Islamic university such as positive emotions toward Islamic-based extracurricular programs. Moreover, open mind on religious moderation has led the students to a multi-ecological moderation needed to achieve tolerance, peace, and openness.